Experiments on punishment and cooperation - Shichman, Ruslan (2019)
Assuming rationality of profit maximising agents, various economic models made specific and testable predictions about human behaviour. These models suggested that costly punishment should be exercised only if future material gains compensate for the incurred costs. The experimental evidence, however, demonstrates that individuals are willing to pay the price to affect the well-being of others even when no pecuniary or reputational benefits can be derived.